How Electronics Knowledge Relates to Industrial Design Education - Yavuzcan, H. Güçlü; Gür, Barış (Design and Technology Education: An International Journal, 2023)
This study has two purposes: To clarify how industrial design relates to electronics knowledge and to determine whether industrial design education is sufficient for teaching it. As digital product design is frequently focused on the design of virtual interfaces until recently, less attention was paid to the design of physical interactions and electronic interfaces. There is increasing interest in electronics education in industrial design, yet electronics is still a bottleneck for many industrial designers. What electronics knowledge industrial designers should have and whether they know it is debatable. Therefore, the study presents a literature review and thematically analyzed interviews to determine its scope. Then, a survey is planned based on the concepts which interviewees remark on. The survey aims to determine whether senior-grade and fresh-graduate industrial designers use correct reasoning in design cases based on electronics. Findings remark that two-thirds of the participants failed in the critical electronics domains and their reasoning scores are distributed equally depending on whether they took electronics courses. Therefore, it is discussed that there is a need for developing a common understanding of the role of electronics in design education. And it is recommended that the approach may focus more on a hands-on terminology education.